THE CORRELATION BETWEEN THE FIRST-YEAR STUDENTS’ VOCABULARY MASTERY AND WRITING DESCRIPTIVE TEXT ABILITY AT SMPN 1 TEBING TINGGI - Fita Maghvira; Eliwarti Eliwarti; Muhammad Syarfi (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
This paper discusses the correlation between two variables, namely vocabulary mastery and writing descriptive text ability of the first-year students, at SMPN 1 Tebing Tinggi. The researcher used a quantitative research method as the data approach. The population was the first-year students with a total of 124 students. The researcher used a simple random sampling technique and selected 32 students from all classes. The instruments used with two types of tests were multiple choice and written tests. To analyze the data, the researcher used SPSS Statistics 25. The research result indicates that the first-year students of SMPN 1 Tebing Tinggi achieved a good level of vocabulary mastery and a mediocre level of writing descriptive text ability. The result indicates that there is a correlation between vocabulary mastery and writing descriptive text ability. The Rxy distribution of the coefficient correlation was 0.408. It means there was a correlation between vocabulary mastery and writing descriptive text ability of the first-year students at SMPN 1 Tebing Tinggi that was at the fair level. Thus, the null hypothesis (Ho) was rejected and the alternative hypothesis (Hα) was accepted.